Cast Metal Surgical Guides: An Affordable Adjunct to Oral and Maxillofacial Surgery. (30th October 2020) - Chakravarthy, Chitra; Aranha, Daisy; Malyala, Santosh Kumar; Patil, Ravi S
Additive manufacturing or 3-dimensional (3D) printing technology has an incredulous ability to create complex constructs with high exactitude. Surgical guides printed using this technology allows the transfer of the virtual surgical plan to the operating table, optimizing aesthetic outcomes, and functional rehabilitation. A vast variety of materials are currently being used in medical 3D printing, including metals, ceramics, polymers, and composites. The guides fabricated with titanium have high strength, excellent biocompatibility, and are sterilizable but take time to print and are expensive. We have thus followed a hybrid approach to fabricate an inexpensive surgical guide using metal where the advantage of 3D printing technology has been combined with the routinely followed investment casting procedure to fabricate guides using nickel–chromium, which has all the advantages of a metal and is cost-effective.